When do firms adjust prices? Evidence from micro panel data - Sarah M. Rupprecht (ETH Zurich, KOF Swiss Economic Institute, 2007)
Using a large panel of quarterly firm survey data from 1984 to 2007, which allow changes in firms' prices to be linked to several firm-specific variables, this paper finds that state-dependent pricing is clearly important in a low inflation environment and that variables measuring the current situation of the firm, especially costs for intermediate products, are important determinants of price adjustments. They add a lot to the explanatory power of a price adjustment probability model, compared to purely time-dependent features. Macroeconomic factors are significant but do not add much in terms of the goodness of fit. Furthermore, when taking into account sticky plan models by excluding possibly predetermined price changes, the importance of state-dependent factors becomes even larger.
Keywords: E31; E32; E50; 330; Price setting behavior; time-dependent pricing; state-dependent pricing; sticky plans; costs; Preiswettbewerb; Preisrigidität; Schätzung; Schweiz